Development of the Pattern Skills Scale for 4-7-Year-Old Children - Ensar YILDIZ; Berrin AKMAN (Hayef: Journal of Education)
The current study aimed to develop a valid and reliable scale to evaluate the patern skills of children between the ages of 4 and 7. For this purpose, the study adopted a survey model. The partcipants consisted of 572 children between the ages of 4 and 7 who contnued their preschool educaton and who contnued their educaton in the frst grade and had not received preschool educaton. The researchers used Microsof Ofce Excel, Factor 12, Lisrel 8.8, and Statstcal Package for the Social Sciences Statstcs sofware, version 24, in the analysis of the data. During the development of the scale, the researchers consulted expert opinions for face validity, used the Lawshe technique for content validity, and performed exploratory and confrmatory factor analyses to ensure construct validity. In order to ensure reliability, the researchers calculated Cronbach’s alpha, Kuder-Richardson (KR-20) internal consistency coefcients, and examined two-half test reliability. In order to test item analysis, the researcher used item difculty and biserial correlaton tests. The results indicated a valid and reliable patern skills scale, consistng of four dimensions and 19 items, with a KR-20 value of 0.83, a two-half test reliability of 0.92, and a Cronbach’s alpha value of 0.87.